A method of optimizing fenestration design for daylighting to reduce heating and cooling loads in offices - Voll, Hendrik; Seinre, Erkki (Journal of Civil Engineering and Management, 2014)
Modern office building designs tend to increase the window share per facade to make the building more impressive with extensive visibility and well daylit rooms. In general, an increased window share results in higher energy usage and higher costs of heating and cooling, but these disadvantages can be reduced with a more careful design. The aim of this paper is to show the influence of window design and room layout on heating and cooling demand and daylight availability in office buildings in northern Europe. The results in the paper are based on design calculations for two different room types and daylight measurements on two room scale models in a daylight laboratory. The calculations show the influence of window design parameters on the cooling and heating demand. The daylight measurements show the influence of window design parameters on the availability of daylight. The results have then been combined to show a feasible window design regarding daylight availability and the resulting cooling and heating demands for different window orientations. The results show that in most cases it is possible to find a combination of window share and window solar factor that is feasible with regard to daylight as well as cooling and heating. The main finding is that there is a smaller or wider range of feasible designs for different window orientations.